Rekrutmen BUMN : Antara Transparansi dan Titipan Jabatan - Fadilla Putri Awalia; Ikwan Arwan (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research study examines the dynamics of organizational communication and public communication in the recruitment process in State-Owned Enterprises (SOEs), with a particular focus on the tension between transparency efforts and the ongoing practice of entrusting positions. Despite the government's introduction of the Joint Recruitment of SOEs (RBB) program, which aims to digitize and standardize the selection of employees, a discrepancy emerges between the program's stated objectives and the perceptions of both the government and the public. The prevalence of complaints pertaining to the absence of information transparency, the lack of feedback mechanisms regarding unsuccessful outcomes, and the emergence of the term